Du tourisme et de l’environnement en Afrique : mariage de raison ou relation d’intérêt ? - Mimoun Hillali (Études Caribéennes)
Africa is seen as a continent both rich and poor, or rather impoverished. However, as the economy of some countries improves, it is starting to interest researchers, economists, businessmen and tourism investors. Do they see it as a future Eldorado or just a juicy vein? Obviously, a good number of courtiers of this promising continent, driven by mercantile interests in the majority, see in this announced progress only its material side: rich lands occupied by poor populations. However, beyond appearances perceived during a lightning tourist stay, this cradle of humanity is intrinsically rich by its human dimension, its cultural diversity, its exceptional biodiversity and, finally, by the richness of its subsoil which arouses the greed of the great powers. But it is also true that this part of the world is relatively poor from an economic, technological and infrastructural point of view; hence the cohabitation between an immense secular heritage and an emerging modernity, poorly assimilated. This ‘exotic’ dualism gave rise to two schools of thought: the followers of the safeguard of the legacies of the past, and the partisans of modern development.What about tourism? Sought after for its contributions and feared for its impacts, it is struggling to find a place in the sun of Africa.